Formation of the market of high-bond (junk bonds) in the United States in 1970–1980 years - Moshenskyi S.Z. (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2017)
Market of high-yield bonds (also known as «junk bonds») began to emerge in the US in the mid-1970s and was associated with the activities of «junk bond king» Michael Milken from Drexel investment company. Junk bonds emitents are small and newly established companies which cannot get a high credit rating. Emission of high-yield (8–10 %) bond was their only chance to find its place in the financial market. Michael Milken realized the potential of these bonds, which, in fact, were often quite reliable securities, and started organizing their emissions by selling junk bonds to Savings and Loan Associations and other investors. In the 1980 issue of such bonds used for aggressive corporate takeovers, which supplied the capital from junk bonds market. Some of takeovers carried out in violation of laws that led to the arrest of Michael Milken, Drexel bankruptcy and the collapse of the entire junk bonds market.